Chemoenzymatic methods for GAG chain editing on proteoglycans - Papadakis, G (2024)
Proteoglycans (PGs) are ubiquitous on the cell surface and in the extracellular matrix of almost all mammalian tissues and comprise one of the most complex and multifunctional glycoprotein families. PGs carry one or more complex glycosaminoglycan (GAG) chains on their protein backbone, which are assembled through a multi-step biosynthetic process. These glycoconjugates regulate diverse functions in mammalian physiology but are typically intractable to precise molecular study due, in part, to the structural diversity of their sugar-polymer glycosaminoglycan (GAG) chains. The lack of methods to isolate or generate native PGs that carry well-defined GAG sequences has posed a major hurdle in dissecting the functional role of the GAG chain and core protein components. This thesis aims to develop a chemoenzymatic method that would enable selective and precise GAG chain editing of heterogeneous GAGs on naturally occurring mammalian PGs. Chapter 1 outlines PG biosynthesis, classification and functions and provides a summary of chemical and chemical biology methods proposed to date for studying, primarily, the function of the GAG-component of PGs. Emphasis was placed on the lack of methods to generate PG constructs that carry well-defined GAG compositions without the need to express specially designed, unnatural protein constructs or use genetically engineered cell lines. In Chapter 2 we show that the heterogeneous chondroitin/dermatan sulfate (CS/DS) GAG chain of tissue-extracted, mammalian PG decorin can be truncated under benign conditions to a well-defined hexasaccharide sequence, terminating on an unsaturated hexuronic acid residue. We then describe robust conditions for biocompatible radical ‘priming’ of the residual hexasaccharide with appropriate thioglycosides for subsequent recognition by glycosyltransferases. We also demonstrate that the efficiency of the radical ‘priming’ conditions developed is similar for both the GAG-truncated decorin scaffold bearing its native N-linked glycosylation, as well as the corresponding N-deglycosylated protein variant. In Chapter 3 we demonstrate that the dual-action glycosyltransferase PmHS2 can engineer heparosan oligosaccharides on appropriately ‘primed’, N-deglycosylated decorin. Investigations into the polymerization activity of PmHS2 in Chapter 4 enabled access to decorin PG bearing a heparosan GAG chain of similar lengths to the naturally occurring CS/DS chains and the retention of all otherwise naturally occurring PTMs, including decorin’s N-linked glycosylation. In Chapter 5, a panel of decorin glycoforms in which we systematically vary their GAG chain composition enabled investigations onto the roles of the GAG chain and the core protein in PG oligomerization, collagen fibrillogenesis and the stimulation of autophagic and pro-inflammatory responses in endothelial cell lines. To the best of our knowledge, this work represents the first strategy that allows access to a well-defined GAG chain composition on a native PG scaffold isolated from a mammalian source. This method could provide a useful tool for deciphering the functional roles of the two major components of PGs in the context of intact glycoconjugates, as proposed in Chapter 6.